Migration and embedding of dental foreign bodies in the soft tissues of the maxilla: A case series. Issue 1 (January 2022) - Ohga, Noritaka; Satoh, Chiharu; Hata, Hironobu; Sakata, Ken-ichiro; Sato, Jun; Kitagawa, Yoshimasa
Abstract: Tracing the movements of foreign bodies is challenging after they aberrantly migrate into the soft tissues. Oral soft tissues are extremely mobile and move in a coordinated and highly complex manner during mastication, deglutition, and phonation. This report presents three cases of aberrantly migrated foreign bodies within the soft tissues of the oral cavity. In the first case, a fractured broach used for root canal treatment entered the oral cavity and moved within the soft tissues, making it difficult to identify its position. In the second case, the tip of a chopstick was embedded within the tissues in the palate, and in the third case, a broken needle was embedded in the left maxilla. It was possible to locate and remove the objects in Cases 1 and 2 (broach and chopstick, respectively); however, attempts to remove the object in Case 3 were unsuccessful due to its location behind the maxillary tuberosity. Foreign bodies that enter into the soft tissues migrate in response to the complex and frequent movements of the oral cavity and, ultimately, get embedded at locations away from their original point of entry. Therefore, dentists need to exercise caution while using instruments such as endodontic file and dental needle, and be completely aware of the difficulties involved in removing migrated and embedded foreign bodies.